Ergonomic Problems and Job Stress: A Study Among Workers at Nichicon (M) Sdn. Bhd. - Nurul Hayati Hanisah, Mohd Sarif (2012)
This research examine the ergonomic issues such as job design, process design work, working time and workload that affect the stress in the workplace. The aim of this study was to develop an understanding of the ergonomic factors that affect stress and to examine the relationship between ergonomic factors and work stress. Data for this study was collected from 100 employees Nichicon (M) Sdn. Bhd., Bandar Baru Bangi, Selangor. The study was carried out by conducting analyses to figure out the relationship that exists between the work design, work process design, working hour and workload with work stress. The results showed a relationship between work load and job stress. The other three variables; work design, work process design and working hour are not significant factors that contribute job stress among the employees. It is essential to promote ergonomics concepts and practice by disseminating the applications to various industries so that both employers and employees benefits and become aware of design concepts and work methods that can help to improve workplace conditions as well as enhancing workers’ OSH.